Influência do solo da fundação no surgimento de eflorescências em edificações no município de Caraúbas/RN - Souza, Sayonara Alves de (Universidade Federal Rural do Semi-Árido, 2018)
Civil construction has been on the rise in last years, however, the presence of construction without the accompaniment of trained professionals able to axuliar during the execution has become commonposition, causing onset of pathological manifestations which influence the useful life of the building. The work was done in the soil foundation of the emergency in the city of Caraúbas - RN. Thus, the studies were carried out in four neighborhoods Caraúbas - RN, the samples composed of soil from three collecions, with the dimensions at 30, 50 and 80 cm, by means of a auger. The samples were conditioned in identified plastic bags. The indices analyzed were: pH; CTC; electrical conductivity and organic matter. The applied methods, in laboratory soil analyzes, are followed by the standards adopted by EMBRAPA (1997). In the electrical conductivity test it is possible to verify that the analyzed inputs do not present a significant salt value, however, the values obtained should not be disregarded, because if there were not a considerable quantity, the apparatus would not perform the reading. The neighborhoods Centro and Leandro Bezerra presented buildings with the pathological manifestation studied and, in the EC test, the respective neighborhoods presented higher conductivity than the others. For pH determination, three neighborhoods, Centro, Nestor Fernandes and Leandro Bezerra, were typically alkaline, characteristic of semi-arid regions. Only the Sebastião Maltese neighborhood showed acidic pH, it can be noticed that the more alkaline, the greater greater the quantity of soluble ions (Ca, Mg, Na, K, H + Al), and the greater the probability of chemical reactions that can make the appearance of pathological manifestation. It is noticed that the CTC is numerically larger for the neighborhoods where the pH has been higher, proving the correlation mentioned above. As in the collection points there was no significant presence of vegetation or animal remains the organic matter test did not show great influence in the conclusion of this work, since its percentage was inferior to 1%, It is thus disregarded as the decisive factor in other parameters, and consequently for pathology studied. From the collected data, it is noticed that the soil of the studied areas tends not to contribute to the appearance of the efflorescence.
Monografia
Keywords: Construção civil; Estudo do solo; Manifestações patológicas; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA